2014
DOI: 10.1016/j.socscimed.2014.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Who donates their bodies to science? The combined role of gender and migration status among California whole-body donors

Abstract: The number of human cadavers available for medical research and training, as well as organ transplantation, is limited. Researchers disagree about how to increase the number of whole-body bequeathals, citing a shortage of donations from the one group perceived as most likely to donate from attitudinal survey data -educated white males over 65. This focus on survey data, however, suffers from two main limitations: First, it reveals little about individuals' actual registration or donation behavior. Second, past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
29
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 36 publications
4
29
2
Order By: Relevance
“…Most of the donors who decided to donate their body to medicine were in their 60s and 70s, which is similar to numerous studies in other countries [ 10 , 11 ], for example: 70.6 years female, 70.2 years male [ 12 ], or 60±15 years for donors in Ireland, 68±13 years for people in New Zealand [ 13 ] or 71.4 years in California, USA [ 14 ]. The gender profile of the investigated population differs from the population gender structure in Poland, having a higher percentage of registered female donors than the percentage of women in the population.…”
Section: Discussionsupporting
confidence: 80%
“…Most of the donors who decided to donate their body to medicine were in their 60s and 70s, which is similar to numerous studies in other countries [ 10 , 11 ], for example: 70.6 years female, 70.2 years male [ 12 ], or 60±15 years for donors in Ireland, 68±13 years for people in New Zealand [ 13 ] or 71.4 years in California, USA [ 14 ]. The gender profile of the investigated population differs from the population gender structure in Poland, having a higher percentage of registered female donors than the percentage of women in the population.…”
Section: Discussionsupporting
confidence: 80%
“…However, this survey contradicted previous studies which found that both married (Bolt et al, ) or unmarried (Boulware et al, ) individuals were more amenable to whole‐body donation. The results of the present study demonstrated that body donation is more likely among separated (divorced and widowed) individuals, which is consistent with some other reports (Fennell and Jones, ; Bolt, ; Asad et al, ). This may suggest that divorced or widowed potential donors are less likely than others to be influenced by their families.…”
Section: Discussionsupporting
confidence: 93%
“…Among 1,605 respondents, 20.87% were willing to donate, while 79.13% were not willing to donate. Although some studies (Dluzen et al, ; Boulware et al, ; Rokade and Gaikawad, ) have reported gender differences in attitudes toward body donation, the present study demonstrated no significant difference between males' and females' willingness to donate, which is largely in agreement with other studies (Anyanwu and Obikili, ; Cornwall et al, ; Asad et al, ). Other factors, such as age and education, might have affected these results.…”
Section: Discussionsupporting
confidence: 92%
“…A recent survey carried out at one of the Polish universities established that the majority of body donors (76.36%) were Catholic (BAJOR et al, 2015). It should be borne in mind that a decision on body donation is influenced in a multi-factorial manner and made through the interplay of various determinants, where religion might or might not play a decisive role (BOLT et al, 2011;ASAD, ANTEBY, GARIP, 2014;KONSCHAKE, BRENNER, 2014). More broadly, a recent study suggested that students' broader, metaphysical belief in the existence of the soul (which might not have religious underpinning) is positively correlated with higher level of stress during dissection (MARTYN et al, 2014).…”
Section: Discussionmentioning
confidence: 99%